2016
DOI: 10.1186/s13148-016-0246-x
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing methylation profiling of subjects with obesity identifies novel gene changes

Abstract: BackgroundObesity is a metabolic disease caused by environmental and genetic factors. However, the epigenetic mechanisms of obesity are incompletely understood. The aim of our study was to investigate the role of skeletal muscle DNA methylation in combination with transcriptomic changes in obesity.ResultsMuscle biopsies were obtained basally from lean (n = 12; BMI = 23.4 ± 0.7 kg/m2) and obese (n = 10; BMI = 32.9 ± 0.7 kg/m2) participants in combination with euglycemic-hyperinsulinemic clamps to assess insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…Furthermore, we set out to identify similarities between whole-blood and the insulin responsive tissue, skeletal muscle. By using skeletal muscle methylation changes assessed in our previous study, 25 we found SLC19A1 to be a blood-based DNA methylation biomarker for that tissue. Not only were these DMCs decreased in methylation in both blood and skeletal muscle, but also the level of change was to a similar extent.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Furthermore, we set out to identify similarities between whole-blood and the insulin responsive tissue, skeletal muscle. By using skeletal muscle methylation changes assessed in our previous study, 25 we found SLC19A1 to be a blood-based DNA methylation biomarker for that tissue. Not only were these DMCs decreased in methylation in both blood and skeletal muscle, but also the level of change was to a similar extent.…”
Section: Discussionmentioning
confidence: 85%
“…27 Interestingly, the distribution pattern of all detected CpG sites were similar to the patterns observed in our previous study in skeletal muscle. 25 The consistent coverage of the genome regardless of tissue type presents RRBS as a viable technique for cross-tissue analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations